2019
DOI: 10.1080/17487870.2019.1609357
|View full text |Cite
|
Sign up to set email alerts
|

How does the flow of remittances affect the trade balance of the Middle East and North Africa?

Abstract: Middle Eastern and North African (MENA) economies have had the highest degree of dependency on received remittances worldwide over the last three decades. The region has also had the highest non-oil external trade balance deficit among developing countries. We examine the role of remittances in the trade balance of 11 labor-abundant MENA countries. Our panel regression analysis shows that the inflow of remittances has had an increasing effect on trade deficits by triggering import-led consumption expenditures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
1
9
0
1
Order By: Relevance
“…Graph 3. Trade balance of the countries Source: The author calculates from research data (World Bank, 2017) Our finding is consistent with the previous results in the evidence of the countries in the Sub-Sahara Africa (SSA) region (Okodua & Olayiwola, 2013) or in the Middle Eastern and North Africa (MENA) region (Farzanegan & Hassan, 2016). Our result is also supported by the studies done by specific country data in Nepal (Bhatta, 2013), in Serbia (Jovicic & Mitrovic, 2006, in Nigeria (Olubiyi, 2014) or Kenya (Kagochi & Kiambigi, 2012).…”
Section: Conducting Research and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Graph 3. Trade balance of the countries Source: The author calculates from research data (World Bank, 2017) Our finding is consistent with the previous results in the evidence of the countries in the Sub-Sahara Africa (SSA) region (Okodua & Olayiwola, 2013) or in the Middle Eastern and North Africa (MENA) region (Farzanegan & Hassan, 2016). Our result is also supported by the studies done by specific country data in Nepal (Bhatta, 2013), in Serbia (Jovicic & Mitrovic, 2006, in Nigeria (Olubiyi, 2014) or Kenya (Kagochi & Kiambigi, 2012).…”
Section: Conducting Research and Resultssupporting
confidence: 90%
“…The quantitative result implied that remittances had a negative effect on exports and a positive effect on imports, so we could think that remittances had a negative impact on the trade balance in the case of the Nigerian economy. Farzanegan and Hassan (2016) identified the role of remittances in the trade balance with a sample including eleven countries in the Middle Eastern and North Africa (MENA) region in 1980-2013. They found that the inflow of remittances had an increasing effect on trade deficit (or negative effect on trade balance) by triggering imported-led consumption expenditures in the economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This appreciation reduces the competitive strength of exports (Okodua and Olayiwola 2013). Moreover, these transfers trigger the consumption expenditures attributable to imports (Farzanegan and Hassan 2016).…”
Section: Madalla and Wu Test (1999)mentioning
confidence: 99%
“…However, the stability of inflowing remittances in Egypt is a critical issue that needs a regular investigation for two reasons. First, remittance flows to the MENA region driven by inflows to Labour Abundant countries (Farzanegan and Hassan, 2016). That makes Egypt the top recipient of remittances in the MENA region.…”
Section: Introductionmentioning
confidence: 99%